Anaesthetic complications in CO2 laser in ENT surgery - Shahnaz Afroza; Md Arif Hossain Bhuyan; AHM Zahurul Huq; A.B.M. Tofazzal Hossain; Lutful Aziz (Society of Otorhinolaryngologists & Head Neck Surgeons of Bangladesh, 2008)
The word laser is an acronym for light amplificationby stimulated emission of radiation and lasertechnology is one consequence of Novel Prize winningin quantum mechanics, which is most important in20th century physical sciences. The rapidadvancement of this technology in ENT surgery hasbeen accompanied by complications, making itimperative that anaesthesiologists as well as ENTsurgeons understand the potential threat to theirpatients and themselves and be preparing to respondproperly. CO2 Laser surgery in ENT is one of thosesurgical procedures in which the surgical risk isminimal while the anaesthetic risk is great. This isbecause of the general problems presented bylaryngeal, pharyngeal and tracheal surgeries combinedwith unique specific problems of the laser